Fuel cell membrane electrode assembly, and fuel cell
Patent Information
- Application Number
- KR1020237016278
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-13
- Filing Date
- 2021-10-07
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2041-10-07
Smart Images

Figure 112023053045961-PCT00002_ABST
Abstract
Description
[0001] The present invention relates to a fuel cell membrane-electrode assembly and also to a fuel cell having improved cell reversal tolerance.
[0002] During the operation of a fuel cell, if the amount of fuel is insufficient and a specific current is recovered simultaneously on the anode of a membrane-electrode assembly (hereinafter MEA), a high potential is generated, which can reverse the voltage of the fuel cell. This phenomenon is generally referred to as "fuel depletion" or "cell reversal." At such high potential, the carbon of the anode catalyst, which is typically used as a support material for Pt-based catalysts at the anode, is oxidized (corroded) and the MEA degrades.
[0003] Various procedures for addressing these problems are disclosed in the prior art. For example, it is possible to use highly graphitized carbon as a support material for platinum catalysts, which is characterized by higher corrosion stability than non-graphitized carbon. Additionally, in order for the anode to provide the current recovered through the oxidation of water to oxygen and thereby protect the carbon from oxidation, it is possible to include a catalytic composition for oxygen evolution (OER) in addition to a hydrogen oxidation catalyst (HOR). Although the described measures already improve "cell reverse resistance" (CRT), these measures are insufficient to achieve the required cell reverse resistance. If fuel depletion occurs too frequently or too regularly, the carbon of the anode catalyst may still corrode, the MEA may fail, and the entire fuel cell may fail. In addition, during the repetitive cycle between low and high potentials at the anode, which occurs under cell reversal conditions or when the fuel cell is initiated under air-air conditions (known as "air-air initiation"), OER catalysts generally based on IrO2 tend to break down and may lose their anode protection ability.
[0004] In addition to the above measures, carbon-free electrodes have also been proposed to improve corrosion stability. In such cases, platinum catalyst particles may be present on a non-conductive support material such as titanium dioxide, and the anode further includes finely dispersed conductive ceramics to ensure sufficient conductivity. For example, one system of this kind WHERE 2019 / 160985 A1It has been proposed. However, these conductive ceramics used as support materials or additives do not have sufficient corrosion stability and tend to decompose, especially in very acidic fuel cell environments. This results in significant power loss and, under certain conditions, contamination of the MEA.
[0005] The object of the present invention is to provide a fuel cell membrane-electrode assembly and a fuel cell that combine high power density, high long-term stability, and simplicity and reliability of manufacturing with high cell reverse resistance.
[0006] The above objective is achieved by the subject matter of the independent claims. The dependent claims include advantageous developments and configurations of the present invention.
[0007] Accordingly, the above objective is achieved by a fuel cell membrane-electrode assembly (fuel cell MEA) comprising a specially implemented support material. The support material comprises a ceramic material and, based on metallic iridium, iridium oxide in a weight fraction of up to 50 wt% based on the total weight of the support material, wherein the ceramic material is present in the form of particles or fibers, more particularly. The iridium oxide may optionally take the form of a mixture with other oxides (hereinafter referred to as iridium oxide) and is particularly deposited on the ceramic material. The iridium oxide exhibits stability against hydrogen reduction, characterized by a weight loss of less than 3 wt% of the support material based on the weight fraction of iridium oxide present in a hydrogen atmosphere.
[0008] In the present invention, the reduction stability of the catalyst of the present invention is determined by measuring the mass or weight loss of the OER catalyst upon exposure to a hydrogen flow at room temperature. This is performed by conducting thermogravimetric analysis (TGA) in a reducing atmosphere. Thermogravimetric analysis of the OER catalyst powder is performed using a Mettler Toledo TGA / DSC 1 instrument. About 10 to 12 mg of OER catalyst powder is weighed into an α-alumina crucible (volume: 70 μL), closed with a perforated α-alumina lid, and introduced directly into a TGA oven. All gases used for thermogravimetric analysis are of 5.0 purity and are commercially available from Westfalen AG. Argon (20 mL min⁻¹) -1 ) is additionally used as a battery carrier gas for hydrogen.
[0009] Each TGA measurement is divided into the following steps:
[0010] i) Drying step within the same reaction system in an oxidizing atmosphere and
[0011] ii) Metal oxide reduction step in a reducing atmosphere.
[0012] The drying step in the same reaction system is used to desorb all organic molecules and water molecules adsorbed on the surface of the OER catalyst powder, and thus the weight loss in step ii) is entirely attributed to the reduction of iridium oxide.
[0013] The procedure for the drying step within the same reaction system is as follows: First, the TGA oven is heated at a temperature of 25°C for 5 minutes using argon (100 mL / min -1 purge with ), and then increase the temperature to O2 (100 mL min -1 From 25℃ to 200℃ (10Kmin) - 1 Raises the temperature to 200℃. O2 (100 mL min -1 Hold for 10 minutes at ). Then, heat the oven to O2 (100 mL min - 1From 200℃ to 25℃ (-10 Kmin) - 1 Cool with ) and finally, bake in a TGA oven at 25°C for 5 minutes in argon (100 mL min -1 Fuzzing with ).
[0014] During the metal oxide reduction step ii), heat the oven to argon (100 mL / min - 1 5 Kmin at ) -1 Heating from to 80°C at a heating rate, then the gas is 3.3 vol% H2 / Ar (40 mL min -1 Switch to ) and maintain at 80℃ for 12 hours. Then, the oven Ar(100 mLmin -1 From 80℃ to 25℃ (cooling rate: -20 Kmin -1 ) Cools down.
[0015] For example, when the support material contains 30 wt% IrO2, the weight loss of the support material in H2 is less than 0.9 wt%, provided that the ceramic material is selected so that almost no weight loss occurs under these conditions. The reduction stability of iridium oxide in the presence of hydrogen is achieved by heat treatment, that is, by thermal conditioning of the support material at a sufficiently high temperature of 400°C or higher, preferably 450°C or higher, more preferably 500°C or higher.
[0016] According to one configuration, a support material is present at the anode of a fuel cell membrane-electrode assembly, and the anode further comprises at least one ionomer and a hydrogen oxidation catalyst, wherein the hydrogen oxidation catalyst comprises particles of platinum and / or platinum alloy disposed on the support material. The hydrogen oxidation catalyst is disposed more specifically on the surface of the support material, and the hydrogen oxidation catalyst and the ionomer are very thoroughly mixed. In this case, the hydrogen oxidation catalyst may be disposed on an iridium oxide and / or ceramic material.
[0017] The above arrangement results in high power density. This is a result of the excellent utilization of platinum, particularly due to the very fine distribution of platinum and / or platinum alloy particles of the hydrogen oxidation catalyst on support materials such as iridium oxide and ceramic materials.
[0018] In an alternative or additional embodiment, the carrier material is present in a barrier layer disposed between the anode and the gas diffusion layer of the membrane-electrode assembly of the fuel cell, and the barrier layer further comprises at least one polymeric binder. Due to the use of a specially implemented support material, the barrier layer is notable for its excellent and reliable productivity, high functionality, particularly high long-term stability, and low cost, and enables excellent cell reversal resistance in a part of the fuel cell MEA.
[0019] Based on the aforementioned observations, the use of stable iridium oxide is particularly important, as such oxides do not dissolve and their OER characteristics are not compromised by repeated potential cycling of the anode between low and high potentials. Stability is achieved by heat-treating the support material at high temperatures to provide the iridium oxide with stability against reduction by hydrogen. In addition to improved stability, the heat treatment of the iridium oxide results in a further reduction in OER activity as a consequence of both a decrease in surface activity and a decrease in surface area resulting from changes in the crystal structure. However, considering the fact that substantially no carbon-based material is present in the layer where the support material is used, cell reversal resistance is excellent, even if the OER activity of the iridium oxide does not reach the maximum possible level. In other words, the permanent retention of iridium oxide activity—that is, the long-term stability of the iridium oxide—is more important than the initial OER activity of the iridium oxide, because the anode and / or barrier layer substantially does not contain carbon and / or carbon-containing support. Here, "substantially not containing carbon and / or carbon-containing supports" means that carbon or carbon-containing compounds are not added to the anode and / or barrier layer. Generally, carbon-containing supports are not polymeric compounds.
[0020] In the absence of carbon materials, the electrical conductivity of the layer is ensured by metals or metal oxides, more particularly iridium oxide and platinum in the anode layer, and also iridium oxide in the barrier layer. Consequently, electrically conductive carbon-containing materials, such as carbon black or graphite, are not used in the anode or any barrier layer present. To achieve effective conductivity and corresponding high-performance capacity in parts of the cell, the metal content in terms of electrically conductive metal compounds must be sufficiently large based on the total weight of the composition of the layer (the weight ratio of the sum of metals to the sum of metals, oxides, and ceramic materials), and must be at least 15 wt%, preferably at least 30 wt%.
[0021] The support material for manufacturing the anode of the present invention and the support material for manufacturing the barrier layer of the present invention are characterized by the same properties as described above, but within the scope of the claims, different parameters may be exhibited within the fuel cell MEA, such as, for example, the weight fraction of iridium, the degree of crystallization of the iridium compound, the chemical composition of the ceramic material, or the BET surface area of the ceramic material.
[0022] In the fuel cell MEA of the present invention, as previously described, high cell reversal resistance is achieved, which is due to the fact that there is no carbon material in the anode and barrier layer, and that the iridium oxide of the support material acts as an oxygen-releasing catalyst that oxidizes water to oxygen, thereby limiting the potential of the anode in the event of fuel depletion and reducing anode stress.
[0023] According to one advantageous development, due to its excellent electrical conductivity and high thermal stability, iridium oxide takes the form of mixtures or alloys with other metal oxides. Examples of metal oxides that can exist as mixtures or alloys with iridium oxide are RuO2, SnO2, and Ta2O5, each with the molecular formula Ir x Ru( 1-x)O2, Ir x Sn (1-x) This results in O2 and mixed oxides of IrO2-Ta2O5. However, iridium oxide must represent the main component and, therefore, to ensure excellent OER activity and stability of the support material, it must represent a weight fraction of more than 50 wt%, more particularly more than 75 wt%, based on the total weight of the mixture or alloy. Iridium oxide is preferably substantially used as a pure oxide of the molecular formula IrO2. Here, the iridium oxide is disposed on the surface of the ceramic material and covers it at least partially.
[0024] The conductivity of the electrocatalyst obtained by platinum or platinum-alloy deposition, as well as the generated conductivity of the support material, can be verified by powder conductivity measurements. A skilled person can further verify the electrical surface resistance within the electrode, for example, in direct fuel cell applications or in four-point measurements, through impedance measurements or polarization curve measurements. On the one hand, heat treatment of the support material induces crystallization of iridium oxide, forming a highly crystalline structure with very high electrical conductivity. On the other hand, heat treatment of the support material can induce aggregation to form larger iridium oxide particles, which exist separated from each other, implying a lack of sufficient percolation pathways for electrons. The best compromise between heat treatment and the amount of metal still depends on the characteristics of the ceramic material used, which can be verified by a skilled person through an appropriate experimental design within the limits defined above.
[0025] According to further advantageous developments for cost reduction, iridium oxide (based on metallic iridium) has a weight fraction of up to 35 wt%, more preferably up to 25 wt%, relative to the total weight of the support material. This kind of low iridium weight fraction also facilitates the possibility of producing these layers by known coating techniques, e.g., knife coating, kiss-roll coating, slot-die coating, screen printing, gravure printing, etc., as it ensures sufficient layer thickness through the use of inert components in the form of ceramic materials in the case of low iridium oxide loading (amount of iridium per unit geometric surface area). Therefore, despite such very low iridium content, the coating of ceramic materials with iridium oxide can be operatively and, in particular, also completely achieved.
[0026] In addition, as an additional advantage, the area weight of iridium oxide in the barrier layer and / or anode is up to 0.05 mg based on metallic iridium. Ir / ㎠, preferably 0.03mg Ir Less than / ㎠, and maximum 0.01mg Ir It is / cm². In this way, productivity can be improved with a low fraction of iridium oxide relative to the total weight of the support material, and since iridium is a very expensive precious metal, a small amount of iridium oxide is also advantageous for lower manufacturing costs.
[0027] In this regard, it is also advantageous for the anode layer thickness containing the hydrogen oxidation catalyst to be, for example, in the range of 0.5 to 2 μm. As a result, a sufficiently large catalyst layer thickness is obtained, which is advantageous for the high-performance capacity of the fuel cell MEA. In particular, a sufficiently large catalyst layer thickness prevents flooding of the anode by water under cold and humid operating conditions. To prevent flooding, additional hydrophobic additives may be used on the anode if necessary, examples of which are perfluorinated polymers such as PTFE.
[0028] As an additional advantage, the ceramic material is a metal oxide, and the metal is selected from the group consisting of titanium, niobium, tantalum, tungsten, silicon, zirconium, hafnium, tin, or mixtures or alloys thereof. The aforementioned metal oxides are notable for their excellent acid stability and corrosion stability. Among these, titanium oxide, niobium oxide, and tungsten oxide are particularly preferred. Additionally, the ceramic material may be doped with a small amount of other metals. According to the present invention, the ceramic material does not necessarily have to be electrically conductive, because electrical conductivity is provided through the use of iridium oxide. As a result, it is possible to achieve excellent electrical conductivity at the anode where particles of platinum and / or platinum alloy are present on the support material, and thus a fuel cell MEA of high power density can be obtained.
[0029] As an additional advantage, the hydrogen oxidation catalyst contains particles of a platinum alloy, wherein one or more alloying elements are selected from the group consisting of ruthenium, rhodium, nickel, copper, and iridium. The alloy metal is notable for its high corrosion stability and thus also improves the oxidation stability of the anode containing the platinum alloy.
[0030] To provide particularly high power of the fuel cell MEA along with very excellent battery reverse resistance, the weight ratio of iridium to platinum of the anode of the support material is preferably 2:1 or less, more preferably 1:1 or less, very preferably 1:2 or less, particularly preferably 1:3 or less, and the weight ratio constituting the weight ratio is based on the amounts of metallic iridium and metallic platinum.
[0031] Considering cost reduction, the area weight of platinum in the anode (based on metallic Pt) is preferably a maximum of 0.1 mg Pt / ㎠, preferably up to 0.05 mg Pt / ㎠, more preferably up to 0.03 mg Pt It is / ㎠.
[0032] To improve the stability of the support material and prevent degradation, the support material preferably has a core-shell structure, where a ceramic material forms the core and an iridium oxide forms the shell. Furthermore, the iridium oxide may only partially cover the underlying ceramic material and form a connected particle structure to create electrically conductive channels within the layer. In the case of the anode layer, electrical connections may also be induced from platinum particles connecting the iridium-covered surfaces.
[0033] Due to its chemical inertness and hydrophobic properties, the polymeric binder of the barrier layer is preferably selected from fluorinated polymers, more particularly polytetrafluoroethylene. Additionally, an ion-conducting polymer binder may be used in the barrier layer. In this case, the binder offers the advantage of promoting the OER reaction through the supply of water near the iridium oxide. For example, a PFSA binder of the same or similar type as that used in the anode may be used. In contrast to the anode, the barrier layer must not substantially contain platinum, particularly near the gas diffusion layer or at the interface. As a result, carbon corrosion of the gas diffusion layer during cell reversal is prevented, ensuring high cell reversal resistance of the MEA.
[0034] 0.05mg Ir Less than / ㎠, preferably 0.03mg Ir Less than / ㎠ and maximum 0.01mg IrA combination of a small amount of iridium oxide in the anode and / or barrier layer per cm² is made possible by using a high fraction of ceramic material containing highly stable iridium oxide. Furthermore, this offers the advantage that only a minute amount of iridium oxide decomposes in the anode and / or barrier layer during anode potential cycling between low and high potentials and in the presence of hydrogen. Consequently, contamination of the MEA by the decomposition of iridium oxide is prevented. In particular, iridium in ionic form cannot pass across the cathode, which can consequently reduce the performance capacity of the MEA. Additionally, especially in the case of the aforementioned small amount of iridium, it is particularly important that the iridium exhibits high stability against decomposition. Otherwise, the iridium will decompose rapidly in the anode due to cycling, and the cell's resistance to reversal will be rapidly lost.
[0035] The support material is obtained by subsequent calcination in an air or oxygen source at a temperature exceeding 400°C, preferably exceeding 450°C, more preferably exceeding 500°C, following the precipitation or deposition (conventional manufacturing) of an iridium precursor material, particularly on a ceramic material. Here, the temperature should not exceed 1000°C to avoid excessive aggregation and loss of specific surface area, and should preferably be less than 750°C, more preferably less than 650°C.
[0036] In addition, the present invention likewise describes a fuel cell comprising a fuel cell membrane-electrode assembly as described above. Due to the use of the fuel cell membrane-electrode assembly for the fuel cell of the present invention, the fuel cell is also notable for its high power density, high long-term stability, the possibility of simple and reliable manufacturing, and high resistance to cell reversal. Brief explanation of the drawing
[0037] Further detailed advantages and features of the present invention are derived from the following description of exemplary embodiments with reference to the drawings, wherein, FIG. 1 shows a cross-sectional view of a fuel cell MEA according to a first embodiment, and FIG. 2 shows a support material for a fuel cell from FIG. 1, and FIG. 3 shows a cross-sectional view of a fuel cell MEA according to a second embodiment. Specific details for implementing the invention
[0038] Only the details essential to the invention are shown in the drawings. All other details are omitted for clarity.
[0039] FIG. 1 shows in detail a fuel cell MEA (1) having a cathode (2), an anode (4), and a membrane (3) between them. The membrane (3) is proton-conductive. The anode (4) comprises a support material (5) homogeneously dispersed in an ionomer (14).
[0040] The support material (5) is illustrated in detail in FIG. 2. The support material (5) takes the form of particles and comprises a ceramic material (6), which is more specifically a metal oxide, and the metal is selected from the group consisting of titanium, niobium, tantalum, tungsten, silicon, zirconium, hafnium, tin, or mixtures or alloys thereof. The ceramic material is notable for its high chemical resistance, particularly under acidic conditions. Since it is chemically inert, it does not affect the reaction in the fuel cell MEA (1) and is not necessarily electrically conductive.
[0041] Particles of iridium oxide (8) are deposited on the surface (7) of the ceramic material (6). The ceramic material (5) and the particles of iridium oxide (8) form a support material. Based on the total weight of the support material (5), the weight fraction of iridium oxide (8) (this value is based on the fraction of metallic iridium) is up to 50 wt%, preferably up to 35 wt%, and more preferably up to 25 wt%. The particles of iridium oxide (8) are notable for their excellent electrical conductivity, which is important for the performance capacity and cell reverse resistance of the fuel cell MEA (1). High cell reverse resistance in the fuel cell MEA (1) is achieved particularly through the omission of carbon material from the anode and also through the effect of iridium oxide (8) as an oxygen evolution catalyst that oxidizes water to oxygen, thereby limiting the potential of the anode in the event of fuel depletion and reducing anode stress.
[0042] Due to the high electrical conductivity of the iridium oxide (8) particles, it is possible to proceed without conventional electrically conductive additives, such as carbon-containing materials, such as carbon black and graphite. Therefore, the anode (4) does not contain carbon material. That is, carbon-containing material is not added to the anode (4). The high stability of the support material (5) against corrosion is notable, and thus there is no degradation due to the oxidation process during the operation of the fuel cell. As a result, high long-term stability with excellent cell reversal resistance is also achieved.
[0043] In an embodiment of the fuel cell MEA (1) illustrated in FIGS. 1 and 2, a support material (5) is present in the anode (4). The anode (4) further comprises at least one ionomer (14) and a hydrogen oxidation catalyst (9), wherein the hydrogen oxidation catalyst (9) comprises particles of platinum and / or a platinum alloy, which, in this case, are disposed on the support material (5), for example. A particularly suitable alloy metal here is selected from the group consisting of ruthenium, rhodium, nickel, copper, and iridium.
[0044] The area weight of platinum in the anode (4) (based on metallic platinum) is more specifically up to 0.1 mg Pt / ㎠, preferably up to 0.05 mg Pt / ㎠, more preferably up to 0.03 mg Pt It is / ㎠. Even with such a small amount of platinum, a fuel cell MEA (1) with very high power density can be achieved.
[0045] The weight ratio of iridium oxide (8) of the support material (5) to platinum of the anode (4) (based on metallic iridium and metallic platinum in each case) is preferably 2:1 or less, more preferably 1:1 or less, more preferably 1:2 or less, particularly preferably 1:3 or less.
[0046] The aforementioned fuel cell MEA (1) is notable for having high power density, high long-term stability, and capacity for simple and reliable production, while also having high resistance to cell reversal.
[0047] FIG. 3 shows a fuel cell MEA (10) according to a second embodiment. The fuel cell MEA (10) again has a cathode (2), a membrane (3), and an anode (4). However, a barrier layer (11) and a gas diffusion layer (12) are also present.
[0048] In the present embodiment, the anode (4) does not contain a support material (however, for example, it may contain one formed by the aforementioned support material), but again comprises a hydrogen oxidation catalyst (9) comprising an ionomer (14) and particles of platinum and / or a platinum alloy. Particularly suitable alloy metals are again selected from the group consisting of ruthenium, rhodium, nickel, copper and iridium.
[0049] The area weight of platinum in the anode (4) is at most 0.1 mg Pt / cm², preferably up to 0.05 mg Pt / ㎠, more preferably up to 0.03 mg PtIt is / cm². As a result of this small amount of platinum, the fuel cell MEA (10) can also achieve a very high power density.
[0050] A barrier layer (11) is provided to improve the cell reverse resistance of the fuel cell MEA (10), and is disposed on the anode side of the fuel cell MEA (10) between the anode (4) and the gas diffusion layer (12). The barrier layer (11) comprises a support material (5) and additionally comprises at least one polymeric binder (13) advantageously containing PTFE.
[0051] The support material (5) may have the same embodiment as the support material from FIG. 2, but does not have a hydrogen oxidation catalyst (9). Accordingly, the support material (5) comprises a fine particle ceramic material (6) having particles of iridium oxide (8) disposed on its surface (7). The area weight of iridium oxide (8) in the barrier layer (11) (this value is based on metallic iridium) is at most 0.05 mg Ir / ㎠ and preferably 0.03mg Ir It is less than / ㎠.
[0052] Even in a fuel cell MEA (10), excellent battery reverse resistance can be achieved through the use of a support material (5) in the barrier layer (11).
[0053] In addition to the written description of the present invention above, for the supplementary disclosure of the present invention, graphic representations of the present invention in FIGS. 1 to 3 are explicitly referred to. Explanation of the symbols
[0054] 1 Fuel Cell MEA 2 cathodes Act 3 4 anodes 5 Support material 6 ceramic materials 7 Surfaces of ceramic materials 8 Iridium oxide 9 Hydrogen Oxidation Catalyst 10 Fuel Cell MEA 11 Barrier layer 12 Gas Diffusion Layers 13 Polymeric binders 14 Ionomer
Claims
Claim 1 A fuel cell membrane-electrode assembly (1, 10), comprising at least one ionomer (14) and an anode (4) comprising a hydrogen oxidation catalyst (9), wherein the hydrogen oxidation catalyst (9) comprises particles of platinum, a platinum alloy, or both, and a support material (5) comprising a ceramic material (6) and an iridium oxide (8), wherein the weight fraction of the iridium oxide (8) is at most 50 wt% of the total weight of the support material (5) based on metallic iridium, and when the support material is exposed to 3.3 vol% hydrogen in argon for 12 hours at a temperature of 80°C, the support material has a weight loss of less than 3 wt% based on the weight fraction of the iridium oxide (8), and the support material (5) is present in the anode (4) of the fuel cell membrane-electrode assembly (1) and the platinum, a platinum alloy, or these Particles of both are disposed on the support material (5), or the support material (5) is present in a barrier layer (11) disposed between the gas diffusion layer (12) and the anode (4) of the fuel cell membrane-electrode assembly (10), and the barrier layer (11) further comprises at least one polymeric binder (13), or the support material (5) is present on the anode (4) of the fuel cell membrane-electrode assembly (1) and particles of platinum, platinum alloy, or both are disposed on the support material (5), and the support material (5) is present in a barrier layer (11) disposed between the gas diffusion layer (12) and the anode (4) of the fuel cell membrane-electrode assembly (10), and the barrier layer (11) further comprises at least one polymeric binder (13), and the area of the iridium oxide (8) in the barrier layer (11), the anode (4), or both. The weight is 0.03 mg based on metallic iridium. Ir Fuel cell membrane-electrode assembly (1, 10), less than / ㎠. Claim 2 delete Claim 3 A fuel cell membrane-electrode assembly (1, 10), wherein the iridium oxide (8) exists as a mixture or alloy with other metal oxides, or the weight fraction of the iridium oxide (8) is at most 35 wt% or at most 25 wt% with respect to the total weight of the support material (5) based on metallic iridium, or the iridium oxide (8) exists as a mixture or alloy with other metal oxides, and the weight fraction of the iridium oxide (8) is at most 35 wt% or at most 25 wt% with respect to the total weight of the support material (5) based on metallic iridium. Claim 4 delete Claim 5 A fuel cell membrane-electrode assembly (1, 10), wherein, in claim 1 or 3, the ceramic material (6) is a metal oxide and the metal is selected from the group consisting of titanium, niobium, tantalum, tungsten, silicon, zirconium, hafnium, tin, or a mixture or alloy thereof. Claim 6 A fuel cell membrane-electrode assembly (1, 10), wherein, in claim 1 or 3, the hydrogen oxidation catalyst (9) comprises particles of a platinum alloy, and the one or more alloy metals are selected from the group consisting of ruthenium, rhodium, nickel, copper, and iridium. Claim 7 A fuel cell membrane-electrode assembly (1, 10) according to claim 1 or 3, wherein the weight ratio of the iridium oxide (8) to the platinum of the anode in the support material (5) is 2:1 or less, or 1:1 or less, or 1:2 or less, or 1:3 or less, based on metallic iridium and metallic platinum in each case. Claim 8 In claim 1 or 3, the area weight of platinum in the anode is at most 0.1 mg Pt / ㎠, or up to 0.05 mg Pt / ㎠, or up to 0.03 mg Pt / ㎠, or the support material (5) has a core-shell structure, or the area weight of platinum in the anode is at most 0.1 mg Pt / ㎠, or up to 0.05 mg Pt / ㎠, or up to 0.03 mg Pt A fuel cell membrane-electrode assembly (1, 10) having a support material (5) having a core-shell structure, with a diameter of / ㎠. Claim 9 A fuel cell membrane-electrode assembly (1, 10), wherein, in claim 1 or 3, the polymeric binder (13) is selected from a fluorinated polymer or is polytetrafluoroethylene, and the anode (4), the barrier layer (11), or both thereof do not contain carbon and carbon-containing compounds, or the polymeric binder (13) is selected from a fluorinated polymer or is polytetrafluoroethylene, and the anode (4), the barrier layer (11), or both thereof do not contain carbon and carbon-containing compounds. Claim 10 A fuel cell comprising a fuel cell membrane-electrode assembly (1, 10) of claim 1 or 3.
Citation Information
Patent Citations
Membrane catalyst layer assembly, membrane electrode assembly, and polymer electrolyte fuel cell
JP2008123728A
catalyst
JP2017533084A
Conductive matrices for fuel cell electrodes
KR1020080009150A
Fuel cell electrode catalyst layer, production method therefor, membrane electrode assembly, and solid polymer fuel cell
KR1020170030584A
Catalyst for anode, reversal tolerant anode for fuel cell and membrane electrode assembly comprising the same
KR1020170125509A
